Race and police brutality: roots of an urban dilemma - Holmes, Malcolm D. (SUNY series in deviance and social control, 2008)
The nature of police brutality -- Social threat and police violence -- Social identity and ingroup bias -- Stereotyping and outgroup bias -- The emotional roots of intergroup relations -- Translating intergroup biases into intergroup aggression -- A social, emotional, and cognitive theory of excessive force -- Can popular policies reduce police brutality? -- Roots of an urban dilemma